Cigarette Smoking, Mental Health, Depression, Maryland Behavioral Risk Factor Surveillance System Survey, 2020 - Balsara, Khushbu; Iftikhar, Ali; Galiatsatos, Panagis; DiClemente, Carlo; Mattingly, Brian; Kanarek, Norma F. (Sage, 2024)
Background Smoking cessation is linked to improved mental health that encompasses the overall well-being and psychological functioning of an individual. Objective Examine relationships between smoking, mental health, and social connectedness among adults in Maryland, US in 2020. Methodology This cross-sectional study used data from the Maryland 2020 Behavioral Risk Factor Surveillance System Survey of adults during the onset of COVID-19. Primary outcomes measured include demographics, depression, and number of not good mental health days among individuals with current and former smoking statuses compared to those who have never smoked. Results Compared to those who never smoked, individuals who currently smoked had an increased relative risk of reporting 14 or more days of not good mental health (RRR = 1.63, 95% CI: 1.35-1.97, P < .001) and a history of depression (RRR = 1.99, 95% CI: 1.69-2.35, P < .001). Individuals with former smoking status also showed elevated risk, with RRR = 1.24 (95% CI: 1.06-1.45, P = .006) for 14 or more days of not good mental health and RRR = 1.46 (95% CI: 1.28-1.66, P < .001) for a history of depression. Widowed, separated, or divorced; unemployed or unable to work; without a high school diploma; or recent physical exam were inclined to have a current or former smoking status. Conclusion We identify critical subpopulations vulnerable to life-long smoking behaviors amid the COVID-19 pandemic including adults under 35 years old, and those suffering from depression, a lack of social connectedness due to unemployment, changes in marital status, and outdated physical exams. The US Surgeon General’s 2023 Advisory on the epidemic of loneliness and the 2021 Youth Mental Health Report emphasize the mental health crises among the young in which these findings serve as a compelling call to action for innovating targeted public health interventions.
Keywords: UMBC HABITS Lab